Long term follow up of radiofrequency catheter ablation of atrial flutter: clinical course and predictors of atrial fibrillation occurrence. Issue 1 (15th December 2003) - Bertaglia, E; Zoppo, F; Bonso, A; Proclemer, A; Verlato, R; Corò, L; Mantovan, R; D'Este, D; Zerbo, F; Pascotto, P
Abstract : Objectives: To evaluate the time to onset and the predictors of atrial fibrillation (AF) during long term follow up of patients with typical atrial flutter (AFL) treated with transisthmic ablation. Design: Prospective multicentre study. Methods and results: 383 patients (75.4% men, mean (SD) age 61.7 (11.1) years) who underwent transisthmic ablation for typical AFL were investigated. In 239 patients (62.4%) AF was present before ablation. Ablation proved successful in 367 patients (95.8%). During a mean (SD) follow up of 20.5 (12.4) months, 41.5% of patients reported AF. The cumulative probability of postablation AF increased continuously as time passed: it was 22% at six months, 36% at one year, 50% at two years, 58% at three years, and 63% at four years. Conclusions: AF occurred in a large proportion of patients after transisthmic catheter ablation of typical AFL. The occurrence of AF was progressive during follow up. Preablation AF, age < 65 years, and left atrial size > 50 mm are associated with postablation AF occurrence.